The optimization of Biodiesel production from Brassica carinata using ultrasonic irradiation-assisted by response surface methodology - Thaiyasuit, Prachasanti (Srinakharinwirot University Engineering Journal, 2018)
This research presents the production of biodiesel from Brassica carinata oil by using ultrasonic irradiation as a reactor. The potassium hydroxide is a catalyst and 40 Hz 400 W ultrasonic irradiation is applied as a reactor. The Response Surface Methodology (RSM) in conjunction with the central composite design (CCD) was used to design the experimental. The process was carried out in a batch laboratory scale. The experiment setup were 5:1–7:1 of methanol to oil molar ratio, 1–2 wt% of catalyst concentration, 35-45◦C of reaction temperature and 6–12 minute of reaction time. From the result, it is found that the maximum percentage of conversion to biodiesel is 99.71% at 5:1 of methanol to oil molar ratio, 2 wt% of the catalyst concentration, 45◦C of the reaction temperature and 6 minute of the reaction time. The predicted optimum conversion to biodiesel percentage by quadratic polynomial is 99.02% at 5:1 of methanol to oil molar ratio, 1.69 wt% of catalyst concentration, 35 ◦C of reaction temperature and 6 minute of reaction time. This conversion to biodiesel percentage have been verified by the 0.9137 of determination coefficient (R2), 0.8332 of the adjust determination coefficient (Adj. R2) and 0.94% of standard error.